2016
DOI: 10.1016/j.celrep.2016.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Vitamin D Availability Impacts Hematopoietic Stem Cell Production

Abstract: SUMMARY Vitamin D insufficiency is a worldwide epidemic affecting billions of individuals, including pregnant women and children. Despite its high incidence, the impact of active vitamin D3 (1,25(OH)D3) on embryonic development beyond osteo-regulation remains largely undefined. Here, we demonstrate that 1,25(OH)D3 availability modulates zebrafish hematopoietic stem and progenitor cell (HSPC) production. Loss of Cyp27b1-mediated biosynthesis or vitamin D receptor (VDR) function by gene knockdown resulted in sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
68
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(79 citation statements)
references
References 53 publications
4
68
0
1
Order By: Relevance
“…However, in a recent publication, it was reported that active vitamin D3 is both necessary and sufficient to modify embryonic hematopoietic stem cell production. This effect is due to vitamin D receptor‐mediated transcriptional activation of the inflammatory chemokine CXCL8, stimulating cell‐autonomous regulation of hematopoietic stem cell expansion and viability via CXCR1/2 activity …”
Section: Discussionmentioning
confidence: 99%
“…However, in a recent publication, it was reported that active vitamin D3 is both necessary and sufficient to modify embryonic hematopoietic stem cell production. This effect is due to vitamin D receptor‐mediated transcriptional activation of the inflammatory chemokine CXCL8, stimulating cell‐autonomous regulation of hematopoietic stem cell expansion and viability via CXCR1/2 activity …”
Section: Discussionmentioning
confidence: 99%
“…In this study, zebrafish morpholino knockdown of essential vitamin D regulatory genes (vdra and cyp27b1) was used to show that calcitriol could modify zebrafish hematopoietic stem progenitor cell production. In addition, exposing human CD34 + umbilical cord HSCs to calcitriol ex-vivo was shown to enhance proliferation, colony forming activity and cell survival [9]. Considering these findings, it is plausible that the patient's leukemic clone co-opted the vitamin D pathway to enhance leukemic cell proliferation without impacting on differentiation.…”
Section: Discussion/conclusionmentioning
confidence: 98%
“…In the aforementioned context, it is not obviously clear why up-regulation of the vitamin D pathway would be advantageous to this patient's leukemic blasts. However, a recent publication intriguingly links vitamin D metabolism to teleost developmental hematopoiesis and human umbilical cord HSC proliferation [9]. In this study, zebrafish morpholino knockdown of essential vitamin D regulatory genes (vdra and cyp27b1) was used to show that calcitriol could modify zebrafish hematopoietic stem progenitor cell production.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Cortes et al [25] have pointed out how vitamin D signaling plays a role in HSPC expansion and survival in zebrafish embryos and human umbilical cord blood. They showed that HSPCs respond directly to [1,25] (OH)D3 stimulation via vitamin D receptor-induced transcriptional activation of the inflammatory cytokine CXCL8. VDR is expressed on human CD34 hematopoietic progenitors [26].…”
Section: Discussionmentioning
confidence: 99%